Cemetery Citizens: Reclaiming the Past and Working for Justice in American Burial Grounds - Rosenblatt, Adam (Stanford University Press, 2024)
Across the United States, groups of grassroots volunteers gather in overgrown, systemically neglected cemeteries. As they rake, clean headstones, and research silenced histories, they offer care to individuals who were denied basic rights and forms of belonging in life and in death. Cemetery Citizens is the first book-length study of this emerging form of social justice work. It focuses on how racial disparities shape the fates of the dead, and asks what kinds of repair are still possible. Drawing on interviews, activist anthropology, poems, and drawings, Adam Rosenblatt takes us to gravesite reclamation efforts in three prominent American cities. Cemetery Citizens dives into the ethical quandaries and practical complexities of cemetery reclamation, showing how volunteers build community across social boundaries, craft new ideas about citizenship and ancestry, and expose injustices that would otherwise be suppressed. Ultimately, Rosenblatt argues that an ethic of reclamation must honor the presence of the dead—treating them as fellow cemetery citizens who share our histories, landscapes, and need for care.